The ecology and evolution of seed predation by Darwin's finches on Tribulus cistoides on the Galápagos Islands. Issue 1 (21st October 2019) - Carvajal‐Endara, Sofía; Hendry, Andrew P.; Emery, Nancy C.; Neu, Corey P.; Carmona, Diego; Gotanda, Kiyoko M.; Davies, T. Jonathan; Chaves, Jaime A.; Johnson, Marc T. J.
Abstract: Predator–prey interactions play a key role in the evolution of species traits through antagonistic coevolutionary arms races. The evolution of beak morphology in the Darwin's finches in response to competition for seed resources is a classic example of evolution by natural selection. The seeds of Tribulus cistoides are an important food source for the largest ground finch species ( Geospiza fortis, G. magnirostris, and G. conirostris ) in dry months, and the hard spiny morphology of the fruits is a potent agent of selection that drives contemporary evolutionary change in finch beak morphology. Although the effects of these interactions on finches are well known, how seed predation affects the ecology and evolution of the plants is poorly understood. Here we examine whether seed predation by Darwin's finches affects the ecology and evolution of T. cistoides . We ask whether the intensity of seed predation and the strength of natural selection by finches on fruit defense traits vary among populations, islands, years, or with varying finch community composition (i.e., the presence/absence of the largest beaked species, which feed on T. cistoides most easily). We then further test whether T. cistoides fruit defenses have diverged among islands in response to spatial variation in finch communities. We addressed these questions by examining seed predation by finches in 30 populations of T. cistoides over 3 yr. Our study reveals three key results. First, Darwin's finches strongly influence T. cistoides seed survival, whereby seed predation varies with differences in finch community composition among islands and in response to interannual fluctuations in precipitation. Second, finches impose phenotypic selection on T. cistoides fruit morphology, whereby smaller and harder fruits with longer or more spines exhibited higher seed survival. Variation in finch community composition and precipitation also explains variation in phenotypic selection on fruit defense traits. Third, variation in the number of spines on fruits among islands is consistent with divergent phenotypic selection imposed by variation in finch community composition among islands. These results suggest that Darwin's finches and T. cistoides are experiencing an ongoing coevolutionary arms race, and that the strength of this coevolution varies in space and time.